The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12250-016-3899-x
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus infection: a global zoonotic challenge

Abstract: Hantaviruses are comprised of tri-segmented negative sense single-stranded RNA, and are members of the Bunyaviridae family. Hantaviruses are distributed worldwide and are important zoonotic pathogens that can have severe adverse effects in humans. They are naturally maintained in specific reservoir hosts without inducing symptomatic infection. In humans, however, hantaviruses often cause two acute febrile diseases, hemorrhagic fever with renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 114 publications
1
112
0
5
Order By: Relevance
“…Moreover the apparent effect of Ribavirin on Hantaviruses, has turned drug research to new nucleoside analogues found to be effective in vitro and in animal studies. For example 1-β-d-ribofuranosyl-3-ethynyl-triazole (ETAR) [1,2,4] has showed significant antiviral activity against hantavirus when administered in doses 12.5-25mg/kg intraperitoneally [33]. On the other hand Arbidol, an immunomodulatory drug, was found to be effective in doses of approximately 80mg/kg/day orally [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover the apparent effect of Ribavirin on Hantaviruses, has turned drug research to new nucleoside analogues found to be effective in vitro and in animal studies. For example 1-β-d-ribofuranosyl-3-ethynyl-triazole (ETAR) [1,2,4] has showed significant antiviral activity against hantavirus when administered in doses 12.5-25mg/kg intraperitoneally [33]. On the other hand Arbidol, an immunomodulatory drug, was found to be effective in doses of approximately 80mg/kg/day orally [34].…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of haemorrhagic manifestations such as hematuria, petechiae, internal haemorrhages and requirement of dialysis treatment, hypotension and fatality incidences are much greater in HFRS caused by DOBV, as compared by NE caused by PUUV or SAAV. Mortality rates in PUUV-HFRS are very low (~0.1%) in comparison with 12% in DOBV infections [2,3]. Patients infected by DOBV present usually more severe symptoms with haemorrhagic manifestations being most dominant (26-59%).…”
Section: Epidemiology Clinical Features and Disease Severity Of Hantmentioning
confidence: 96%
See 2 more Smart Citations
“…The Hantavirus is a member of the Bunyaviridae family and the genus includes N 50 different viruses that manifest with a wide spectrum of clinical illnesses [26]. The pathogenesis of Hantavirus is related to the targeting of vascular endothelial cells, alveolar macrophages and follicular dendritic cells, as well as the renal tubular epithelium [27].…”
Section: Hantavirus Pulmonary Syndromementioning
confidence: 99%